Synthesis, Characterization and Antioxidant Evaluation of New N-Α-Chloroacetylsalicyloyl-N-Antipyrine Benzamide - Abdalrahem Bin Selim, Elham; Hadi Al–Douh, Mohammed; Abdulaziz Bin Hawiel, Faten (Al-Nahrain Journal of Science, 2024)
The new compound N-α-chloroacetylsalicyloyl-N-antipyrine benzamide was synthesized by a reaction of N-benzylidene antipyrine amine and O-acetyl salicyloyl chloride. On the other hand, N-benzylidene antipyrine amine was obtained by a coupling reaction between benzaldehyde and 4-aminoantipyrine, while O-acetyl salicyloyl chloride resulted from acylation reaction of aspirin starting from salicylic acid. All synthesized compounds were characterized by using m.ps., UV-Vis., FTIR, MS, and 1HNMR spectroscopic methods. The method of DPPH was also used as testing to measure the radical scavenging of the new compound. It showed very powerful antioxidant activity with IC50 value of 29 ppm. Moreover, its antibacterial activity  was tested against three types of bacteria.